ANALISIS YURIDIS PERTANGGUNGJAWABAN PENGURUS TERHADAP ANGGOTA ATAS PENGELOLAAN KOPERASI SIMPAN PINJAM YANG DINYATAKAN PAILIT BERDASARKAN UNDANG-UNDANG NOMOR 25 TAHUN 1992 TENTANG PERKOPERASIAN DIKAITKAN DENGAN PRINSIP KEHATI-HATIAN - Jhonson Datmalem Siahaan; Maryati Bachtiar; Dasrol Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Cooperatives are a form of cooperation in the economic field which is held on the basis of thesimilarity in the types of fulfillment of life needs. In accordance with the provisions contained in article16 of the Law of the Republic of Indonesia Number 25 of 1992 along with an explanation stated that"the type of cooperative is based on the similarity of activities and economic interests of its members".Basic To determine the type of cooperative is the similarity of activities, interests and economic needsof its members, such as among others savings and loan cooperatives (Credit Cooperatives).Cooperatives in the context of running a business, have administrators who are devices of cooperativesthat are domiciled as members of the meeting. The formation of administrators is chosen from and bycooperative members in a member meeting forum for savings and loan cooperatives. so that in this casethe management is the person entrusted with managing the savings and loan cooperative and at thesame time as a person who can be held accountable if the savings and loan cooperative is declaredbankrupt either because of its negligence or because of intent. so that in this case the management mustprioritize the principle of prudence in managing the savings and loan cooperativeThe purpose of this thesis is: first To find out the responsibility of the management of themembers for the management of savings and loan cooperatives declared bankrupt based on law number25 of 1992. second, to know the ideal responsibility by the management of members for themanagement of savings and loan cooperatives is associated with prudence be careful.This type ofresearch is normative legal research or also called doctrinal legal research and this research isdescriptive. using legal principles, the data sources used in this study are secondary data, namely dataobtained from the literature such as legal journals, books, judge's decisions relating to research. Dataanalysis is done qualitatively and deductively withdrawnFrom the results of this study there are two main problems that can be concluded, first, that,Putusan Nomor:06/Pdt.Sus, Pembatalan Perdamaian/2016/PN.Niaga.Jkt.Pst. Jo Nomor:11/PKPU/2014/PN.Niaga.Jkt.Pst, (in accordance with the provisions of Article 34 of the cooperativelaw). So that in the case of the decision the KCKGP management did not have good faith in carryingout the request for peace (Homologation) which in the application should have the opportunity to savethe cooperative so that it was not declared bankrupt by conducting the appropriate agreement, second,the manager's ideal accountability must carry out the precautionary principle to maintain cooperativehealth and the management must have a moral responsibility to compensate both the managementtogether in a joint manner or by giving personal property without imposing any rights on the membersof the cooperative, because in this matter is fully administered by people who are given responsibilityand trust in managing cooperatives.Keywords: Cooperatives, Management of Cooperatives, Bankruptcy and the Precautionary Principle